OPTIMIZATION INVENTORY MANAGEMENT AT SHOPEE INDONESIA: KEY TO IMPROVING EFFICIENCY AND CUSTOMER SATISFACTION - Rizki Agung Ramadani; Berliyana Kesuma Hati; Zefri Setiawan (PT. Media Akademik Publisher, 2024)
Inventory management system is a crucial component in e-commerce, including on the Shopee Indonesia platform. This study aims to evaluate the effectiveness of the current system and identify existing and proposed practices to improve Shopee's operational efficiency. The results of the analysis show that the inventory management system in Shopee Indonesia has been designed to support the smooth flow of goods. However, based on interviews with several warehouse managers and users, there are several challenges in realizing the expected practices, such as less than optimal product tracking and data handling that requires regular updates. Shopee uses sophisticated technology to manage inventory, but there are opportunities to improve data accuracy and responsiveness to changes in market demand. Among the existing practices, the use of algorithms for demand prediction shows positive results, but the implementation of these practices still requires adjustments. This study proposes several strategic steps, including improving serious system integration between inventory management and sales systems, as well as continuous training for employees. In addition, improving the real-time monitoring system will support better and faster decision making in terms of procurement and delivery of goods. Overall, although the inventory management system in Shopee Indonesia has shown effectiveness in many aspects, this study emphasizes the need for innovation and implementation of best practices to overcome existing weaknesses. Thus, it is expected that there will be a significant increase in operational efficiency, which will have a positive impact on user experience and customer satisfaction.